The Foreign Policy of Iran Towards Arabian Gulf (The Horizon of Future) - اسراء شريف الكعود (College of Education for Women, 2019)
Iran Regional and Foreign Security Policies Gulf. The long history of regional and other conflicts which their severity increased because of appearance of modern states and cultural and lingual ancient differences resulted in deep feeling of doubt and suspicion between Iran and its Arab neighbors .Meanwhile the two sides have several interests common points , the moist important is the strategic and commercial interests . The fears and objective procedures based on the continuing evaluation of Iran abilities and needs direct security policies in internal and foreign affairs concerning the world in Gulf specially.